2008
DOI: 10.1108/00242530810911789
|View full text |Cite
|
Sign up to set email alerts
|

How do school resource centre staff deal with information requests?

Abstract: PurposeThe purpose of this paper is to use new data to explore the pertinence, to the work of an information professional dealing with inquiries, of an existing typology indicating the forms of action taken by people when approached for information by youngsters.Design/methodology/approachThe study featured here drew on qualitative data from a transaction log maintained in the resource centre of an English high school and from two interviews with the information specialist employed.FindingsBroadly, the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Insight into the former is derived from outcomes arising from a previous research project undertaken by the author. 10 In this study, he worked closely with an intermediary employed in the resource center of an English high school catering to 13 to 18 year olds. Over a week-long period, the information specialist maintained a log in which he recorded all the inquiries he handled and the initial steps he took to resolve them.…”
Section: Scope Of the Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Insight into the former is derived from outcomes arising from a previous research project undertaken by the author. 10 In this study, he worked closely with an intermediary employed in the resource center of an English high school catering to 13 to 18 year olds. Over a week-long period, the information specialist maintained a log in which he recorded all the inquiries he handled and the initial steps he took to resolve them.…”
Section: Scope Of the Articlementioning
confidence: 99%
“…40 In the years that immediately followed, Shenton was intrigued by whether the typology of their actions accurately represented the ways in which library staff in schools respond to queries from students. To explore further, a new study undertaken in an English high school that had not been involved in the original project was designed, 41 and the typology discussed in this article was created from the data collected in this project. The results were broadly similar, with all but two of the original categories of action emerging and only one more having to be created.…”
Section: Future Research and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The innovations failed to have the desired effect, however, and, in the subsequent months, there was little evidence of even hybrid use of materials, despite the fact that books and electronic sources were freely available in the same room. A later study (Shenton, 2008b) revealed that when learners needed material from books during a week-long period of data collection, they were less comfortable than when using the Web and in several instances had to approach the information specialist for assistance. In another project, Shenton (2007a) noticed that some of the students' assumptions with regard to library housekeeping were grounded in ignorance, thus again reflecting the learners' lack of knowledge with respect to the 'book' dimension of the independent learning area.…”
Section: Learners' Interaction With Informationmentioning
confidence: 99%
“…The foci of two papers are especially pertinent. In the first (Shenton, 2008a), he considers the different forms of behaviour, and their prevalence, exhibited by users of the computer workstations within the facility, whilst in the second (Shenton, 2008b), he examines the queries presented to the information specialist by centre users and the action he took in response.…”
Section: Introductionmentioning
confidence: 99%